OP0021 A phase 2 study of multiple subcutaneous doses of LY2439821, an anti-IL-17 monoclonal antibody, in patients with rheumatoid arthritis in two populations: Naïve to biologic therapy or inadequate responders to tumor necrosis factor alpha inhibitors. (23rd January 2014) - Genovese, M.; Greenwald, M.; Cho, C.-S.; Berman, A.; Jin, L.; Cameron, G.; Wang, L.; Xie, L.; Braun, D.; Berclaz, P.-Y.; Banerjee, S.
Abstract : Background: IL-17A (IL-17) is a potential therapeutic target for rheumatoid arthritis (RA) therapy. Objectives: To evaluate an anti-IL-17 monoclonal antibody, LY2439821 (LY), for safety and efficacy in 2 populations: naïve to biologic therapy (bDMARD naïve) or inadequate responders to tumor necrosis factor (TNF-IR). Methods: In this randomized, double-blind study, 260 bDMARD naïve patients (pts) received subcutaneous placebo (PB) or LY (3, 10, 30, 80, or 180 mg) and 188 TNF-IR pts received PB or LY (80 or 180 mg) at Weeks 0, 1, 2, 4, 6, 8, and 10 with concomitant DMARD therapy. The objectives were to determine the dose-response relationship of LY in bDMARD naïve pts based on the ACR20 response rate (primary) by logistic regression at Week 12, and to evaluate efficacy and safety (secondary). Results: There was a significant dose response relationship in bDMARD naive pts at week 12 (p=0.031 using ACR20; p<0.001 using DAS28-CRP). Significant differences vs. PB were seen for DAS-28 CRP reductions in bDMARD naïve pts and in TNF-IR pts at all LY doses, with a rapid onset of efficacy within 1 week after the first dose and with increasing magnitude of reductions with increasing doses (Figure). In both populations, significant differences vs PB were observed for other clinical measures. The frequency of treatment-emergent adverse events (TEAEs) was similar across treatment arms (range: 45-64%). Infections were more frequent in LY arms combined compared to PB in bDMARD naïve (25 vs 19%) and TNF-IR pts (27 vs 23%) with no observed dose relationship. In bDMARD naive pts, SAEs occurred in 1 (2%) PB and 7 (3%) LY pts (6 treatment emergent) with 1 serious infection-related event in a pt receiving LY 80 mg. In the TNF-IR population, SAEs occurred in 1 (2%) PB pt and 12 (10%) LY pts (10 treatment emergent), and serious infections occurred in 4 (3%) pts in LY arms combined. Conclusions: LY significantly improved signs and symptoms of RA compared to PB with the best evidence of dose response seen using the DAS-28. The safety profile was comparable to other biologic therapies with no unexpected safety concerns. Disclosure of Interest: M. Genovese Grant/Research support from: Eli Lilly and Company, Consultant for: Eli Lilly and Company, M. Greenwald Grant/Research support from: Eli Lilly and Company, C.-S. Cho Grant/Research support from: Eli Lilly and Company, A. Berman Grant/Research support from: Eli Lilly and Company, L. Jin Employee of: Eli Lilly and Company, G. Cameron Employee of: Eli Lilly and Company, L. Wang Consultant for: Pharmanet/I3, L. Xie Employee of: Eli Lilly and Company, D. Braun Employee of: Eli Lilly and Company, P.-Y. Berclaz Employee of: Eli Lilly and Company, S. Banerjee Employee of: Eli Lilly and Company